Evaluation of augmented reality applications as an interactive learning media for the female reproductive system - Devy Kurnia Ramadhani; Agus Sugiono (Health Educational Laboratory, 2025)
The use of augmented reality (AR) technology in health education is growing rapidly due to its ability to provide interactive and immersive learning experiences. However, research that comprehensively evaluates the feasibility of AR applications on female reproductive system material is still limited. This study aims to evaluate the feasibility of an augmented reality (AR)-based application as an interactive medium in learning about the female reproductive system. The evaluation was conducted on four main aspects, namely: software engineering, learning design, visual communication, and user acceptance. The research method used is a quantitative descriptive approach with data collection techniques through assessment questionnaires by experts and end users (students). The evaluation results show that the software engineering aspect obtained a feasibility score of 82% (excellent feasibility), the learning design aspect 85% (excellent feasibility), the visual communication aspect 71% (good feasibility), and the user acceptance aspect 85% (excellent feasibility). These findings indicate that the developed AR application is generally very suitable for use as a learning medium, especially in supporting the understanding of the concept of the female reproductive system interactively and contextually. However, the visual communication aspect still requires improvement to optimize the user experience. This research contributes to the development of innovative learning media in the field of health education and opens up opportunities for further research that tests the effectiveness of learning quantitatively and in the long term.